Nonmedical Use of Cough Syrup Among Secondary Vocational School Students: A National Survey in China. Issue 10 (March 2016) - Wu, Qingfeng; Yu, Jincong; Yang, Chengwu; Chen, Jiayan; Yang, Longyu; Zhang, Hui; Teng, Shiwei; Li, Jiang; Yan, Dong; Cao, Jiepin; Zhao, Yanting; Wang, Zengzhen
Abstract : Abstract: Nonmedical use of cough syrup (NUCS) among secondary vocational school (SVS) students has been an increasing concern for public health in China, but no data were available. This cross-sectional study aimed to investigate the epidemiological characters of NUCS as well as its risk factors among SVS students in China. From September 2013 to December 2014, a total of 13, 614 SVS students were purposively selected through multistage sampling in 6 cities of China. Information on NUCS, demographics, family background, smoking and alcohol consumption, impulsiveness, sensation seeking, and parental monitoring were collected. Logistic regression was used to explore factors related to NUCS. The 12, 923 (94.9%) valid responses (16.3 ± 1.0 years old, and 52.6% men) reported 3.47% (95% confidence interval: 3.15–3.79%) lifetime NUCS. Logistic regression indicated that smoking, part-time job experience, high level of impulsiveness, and sensation seeking were risk factors for NUCS, whereas urban living and high parental monitoring were protective ones. NUCS was prevalent among SVS students. Interventions that target on smoking, impulsiveness and sensation seeking control, improvement on parental monitoring may have considerable impact on NUCS among SVS students.